Preserving water reserves by collecting and using rainwater: Study of the state of public equipment, especially educational ones - Hanafi, Abdelhakim; Chirou, Yacine; Alkama, Djamal (Journal of Human Sciences, 2023)
Enter With the increase in world population; it has reached, according to the latest statistics, 08 billion people [1]. And therefore the phenomenon of climate change and global warming has worsened [2], as well as the rise in temperatures, which has led to a drop in the level of drinking water and irrigation water at the same time, which aggravates the problem of water scarcity and threatens to spread future wars [3]. It is important for us, as intellectuals, to think seriously about practical and appropriate solutions for our region and our cities and within the framework of our intellectual, scientific and technological capacities, in the sense of finding practical solutions that can be embodied and carried out in the short, medium and long term. This article is the conclusion of a long research on practical (operational) solutions and their application at the level of public equipment, in particular schools (educational), so that we can contribute to the collection and exploitation of rainwater, on the one hand, and restore a general culture to our children.